ENCRYPTION AND DECRYPTION OF AUDIO SIGNAL BASED ON RSA ALGORITHN - Yousif, Sura F. (International Journal of Engineering Technologies and Management Research, 2018)
One of the most important methods to protect and verify information that are exchanged over public communication channels in the existence of third party called antagonists is encryption. The stored or transmitted message is transformed in the encryption process to unreadable or gibberish form. The reverse process in which the intendent recipient can reveal the encrypted message content is called decryption. The encryption and decryption processes are achieved using secret keys that are exclusively exchanged between the sender and recipient. This method can be applied to any form of message such as audio, video, image or text data. The current work applies the well-known RSA algorithm for audio signal encryption and decryption. The performance of the presented algorithm has been tested via experimental implementation which show that the Cpestral Distance Measure (CD), Linear Predicative Code Measure (LPC) and Segmental Spectral Signal to Noise Ratio (SSSNR) reach to 6.8781, 4.9614 and -21.5563 dB respectively using Matlab simulations. The results on the presented technique validated that it is secure, reliable and efficient to be applied in secure audio communications as well as it performed high intelligibility of the recovered audio signal.